Aktivitas Enzimatik Cendawan dari Lalat Bactrocera dorsalis sebagai Kandidat Cendawan Entomopatogen - Rizka Dwi Damayanti; Emantis Rosa; Wawan Abdullah Setiawan (Institut Pertanian Bogor, 2024)
Extracellular enzymes produced by fungi can serve as a screening tool for entomopathogen candidates. Enzyme secretion ability is important in determining the virulence level of an entomopathogenic fungus. This study aims to see the potential of fungal isolates through chitinolytic, lipolytic, and proteolytic activities of five entomopathogenic fungal isolated from Bactrocera sp. imago from citrus plants. The research was carried out at the Microbiology Laboratory of the Department of Biology at the University of Lampung. Enzymatic activity is known through the method of observing the clear zone formed on agar media. Quantitative tests based on the calculation of enzymatic index values showed that Nigrospora sp. (IB1) had lipolytic activity, Penicillium sp. 2 (IB5) isolates had chitinolytic, lipolytic, and proteolytic activities. The isolates of Penicillium sp. 1 (IB2), Phytopthora sp. (IB3), and Gliocladium sp. (IB4) did not show the activity of the three enzymes. Keywords: Bactrocera sp., bioinsecticide, entomopathogenic fungi, enzyme